2010
DOI: 10.1677/erc-10-0002
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine complications in long-term survivors of childhood cancers

Abstract: Endocrine disturbances are among the most frequently reported complications in childhood cancer survivors, affecting between 20 and 50% of individuals who survive into adulthood. Most endocrine complications are the result of prior cancer treatments, especially radiotherapy. The objective of the present review is to discuss the main endocrine complications observed in this population, including disorders of the hypothalamic-pituitary axis, disorders of pubertal development, thyroid dysfunction, gonadal dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
153
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(160 citation statements)
references
References 159 publications
(89 reference statements)
1
153
0
6
Order By: Relevance
“…Moreover, the length of clinical follow-up needs to be considered in this context as the majority of irradiation induced thyroid malignancies arise O10 years after local radiotherapy. It appears possible that the median time of clinical follow-up was too short in our current study and therefore no significantly elevated incidence of secondary malignancies was observed in any location as exemplarily depicted for thyroid neoplasia (14,38). Almost half of all male participants in our study reported on reduced libido and/or erectile dysfunction.…”
Section: Clinical Study J Gebauer E-m Fick and Others Endocrine Latementioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, the length of clinical follow-up needs to be considered in this context as the majority of irradiation induced thyroid malignancies arise O10 years after local radiotherapy. It appears possible that the median time of clinical follow-up was too short in our current study and therefore no significantly elevated incidence of secondary malignancies was observed in any location as exemplarily depicted for thyroid neoplasia (14,38). Almost half of all male participants in our study reported on reduced libido and/or erectile dysfunction.…”
Section: Clinical Study J Gebauer E-m Fick and Others Endocrine Latementioning
confidence: 67%
“…International studies including a systematic clinical follow-up on extended cohorts revealed that the risk of relapse decreases with an increasing time interval to the initial diagnosis; in contrast, the incidence particularly of endocrine late effects remains significantly elevated for many years even in the absence of any signs of relapse from the initial malignant disease. These data are almost exclusively derived from paediatric cancer survivors with a prevalence of at least one chronic disease in up to 70% of cases 30 years after initial diagnosis and about 50% related to an endocrine disorder (13,14). These effects are frequently associated with unspecific symptoms such as fatigue and impaired capability of physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…This cumulative incidence is much higher than that reported by Chow et al (15-year cumulative incidence of hypothyroidism: 1.6%), probably because their study also included patients treated with chemotherapy alone, and because the methodology used may have undervalued the incidence of hypothyroidism (retrospective study, self-reported thyroid dysfunction). 4 Primary hypothyroidism has been linked to exposure to thyroid radiation, 25 primarily in solid tumors such as Hodgkin lymphoma 15,16 and brain tumors, 10,14 although it was also found to be associated with cranial or craniospinal irradiation in patients with childhood acute leukemia. 4 Cranial irradiation in patients with acute lymphoblastic leukemia has long been suggested to play a role in hypothyroidism, 3,4,26 although a few authors have argued that the impact of prophylactic cranial radiation is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…17 According to the literature, the risk of primary hypothyroidism seems to be strongly associated with the total irradiation dose received by the thyroid gland. 25 It has been suggested that the risk of hypothyroidism is higher in patients exposed to craniospinal irradiation than in those who undergo cranial irradiation. 4 We, however, did not find similar results, which may be due to the small number of patients who received craniospinal irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation